Use of conductivity to indicate long-term changes in pollution processes in Lake Taihu, a large shallow lake - Wu, Tianhao; Zhu, Guangwei; Zhu, Mengyuan; Xu, Hai; Zhang, Yunlin; Qin, Boqiang (Environmental science and pollution research international, 2020)
Conductivity is a very reliable, sensitive, and easily obtained indicator of surface water conditions; however, whether it could be used to evaluate lake pollution is less understood. To verify the effectiveness of using conductivity to evaluate the pollution status in lakes, Lake Taihu was analyzed, the third largest freshwater lake in China, which provides drinking water to about 10 million of residents. We analyzed 25-year conductivity data in 32 sampling sites in Lake Taihu, in relation to human population, industrial development, and GDP. The results showed that the conductivity first increased and then decreased following rapid economic growth and subsequent strict pollution control activities. The conductivity is related to industrial sewage ( r = 0.90); SO 4 2− and Cl − concentrations in the water were closely related to the industrial production value ( r = 0.98, 0.99) before 2007. The conductivity increased rapidly from 1992 to 2007 due to eutrophication processes. After 2007, with the implementation of various pollution control measures, the pollution situation gradually abated. The conductivity was closely related to the concentrations of nitrogen and phosphorus ( r = 0.53, 0.14) in Lake Taihu, which suggests that conductivity could be indicator of eutrophication in lakes to some extent. Based on the research results, conductivity can largely be used to characterize the impact of human activities on lakes. Our study suggests that conductivity is a very reliable parameter for evaluating lake pollution. In addition to providing ion information, this measurement could successfully determine pollution sources and restoration effectiveness in lakes, such as ecologically complex Lake Taihu.